The labor market worsening effects of a resource bust: Evidence from the crude oil price shock in Ecuador - Sergio Parra-Cely; Wladimir Zanoni (Inter-American Development Bank (IDB), 2022)
To assess the effects of an oil price bust on individual labor market outcomes, we leverage the 2015 exogenous decline in international oil prices with geographical variation in oil-dependency in Ecuador. To account for propagation mechanisms, we also test the causal effect of the oil price bust on public transfers to local autonomous governments. Reduced form results suggest a moderate oil price pass-through channel on wages and nonlabor earnings but not on labor supply and participation. Public transfers play an amplification role, as a one percentage point decrease in these funds implies workers in oil-dependent areas to experience a wage reduction of 1.5%. Spillover effects to nonextractive industries, with reduced economic activity at the firm level, seem to be the transmission channels explaining the drop in individual earnings during the oil price bust.
Keywords: J21; J22; J30; H41; H72; I31; 330; Resource bust; wages; employment; oil; public transfers; Ecuador